The Effectiveness of Students’ Listening Skill by Using Podcast at The Second Grade of SMK Negeri 6 Balikpapan - Wulandari, Tasya; Sya’ya, Nadia (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2021)
Listening is one of necessary skill in learning English and also the patent skill in English language beside speaking, writing, and reading. Listening is considered as the most basic skill because it is firstly used by learners when they begin to learn a language, especially spoken language. In addition, unconsciously, listening is much more used in classroom than other skills. Nowadays, listening is the most difficult skill for many students to understand. The aim of this research was to find out the empirical data which could determine whether there is a significant effect of using podcast on students‘ listening skill at the second grade of SMK Negeri 6 or not. The method used was quantitative method with quasi-experimental research as its design. The samples of this research were 25 students of TITL 1 class as the experimental class and 25 students of TITL 2 class as the controlled class. Those samples were elected by using purposive sampling. To collect the data from both classes, this research used a listening test provided in a pre-test and post-test as the research instrument. Based on the result of the research, data from both pretest and post-test were calculated and analysed by using IBM SPSS Statistic 21. And the result revealed that the post-test mean score of the experimental class was greater than that of the controlled class, namely (80.88 > 77.04). It meant that the experimental class and the controlled class were different significantly in their posttest mean score. Then, the result of hypotheses analysis showed that tobserve was higher than ttable (2.098 > 1.677) and the significance 2-tailed (P) was lower than the alpha (0.041 < 0.05). It meant that H0 was rejected and Ha was accepted. Thus, it can be considered that using podcast has given significant effect on students‘ listening skill. In addition, the result was also measured by using cohen‘s d effect size measurement to know the strenght of the effect. And the result showed that using podcast in teaching listening gave a moderate effect on students‘ listening skill with the effect size of 0.51.